Empowering Nagaland: Strengthening Health and Education for a Brighter Future - Bideno R Ezung (Universitas Efarina, 2024)
Nagaland is a culturally rich and beautiful state located in the northeastern part of India, The state faces several developmental challenges despite its potential. With its diverse ethnic communities, the rich cultural heritage, and the breathtaking landscapes, has much to offer. However, the state progress has been hindered by various socio-economic challenges, particularly in the sectors of health and education. These two fundamental aspects play a vital role in determining the well-being and development of a state’s population. For Nagaland to bring out its true potential and secure a brighter future, significant investments and strategic reforms in healthcare and education are essential.